Drei Jahrzehnte area-basierte Stadtpolitik in Frankreich: politique de la ville. Bearbeitung gesellschaftlicher Probleme mittels raumorientierter Ansätze? - Glasze, Georg; Weber, Florian (Raumforschung und Raumordnung, 2010)
Since the 1970s, measures have been taken in France to fight a concentration of social and town planning problems by subsidizing certain town quarters in a specific way. The article argues that social problems are eventually being treated as problems of certain quarters. The historical background of the urban development in French suburbs will be described as well as the objectives and measures of the politique de la ville. The massive riots of 2005 in the suburbs have led to a basic criticism of the space-oriented approach of the politique de la ville. Against this background, it will finally be discussed if and, where applicable, in which way the politique de la ville has undergone a basic reorientation in the last few years.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IG.LGIPDK.dreija